Human in vivo talocrural contributions to ankle joint complex kinematics during walking, running, and hopping - Anja-Verena Behling; Lauren Welte; Michael J. Rainbow; Luke Kelly (Heliyon)
The human ankle joint complex, consisting of calcaneus, talus, and tibia, is often simplified as a single functional ankle joint, neglecting the motion of the talus. Understanding the individual contributions of the talus and calcaneus is crucial for comprehending ankle joint complex function in healthy populations, and alterations in function that may exist in clinical conditions.To achieve accurate bone kinematics, high-resolution biplanar videoradiography was used with participants engaged in walking and running (n = 9) and hopping (n = 9) with no overlap in participants. The rotation axes for the calcaneus and talus were analysed relative to the tibia over the ankle joint dorsi-/plantar flexion phases. Contributions of the talocrural joint to overall ankle joint complex function were measured by comparing the range of motion (talus relative to calcaneus).Most of the sagittal plane motion in the ankle joint complex (80%) occurred in the talocrural joint, with the subtalar joint contributing 20%. Rotation of the calcaneus about the tibia dominated frontal and transverse plane motion during hopping. Although surprisingly large ranges of talus motion were also observed in these planes (>5deg), indicating notable inter-subject variability and that the talocrural joint is not a simple hinge joint.The study highlights the importance of directly quantifying talus motion to understand ankle joint complex function. The results showed opposing talus and calcaneus movements for many participants during different locomotor tasks, which may influence the magnitude and distribution of subtalar joint loading. In addition, the large out-of-sagittal plane movements and inter-subject variability in talus and calcaneus motion may further emphasize the need for personalised models to investigate treatments for ankle pathologies.